Biopriming with liquid biofertilizers enhances productivity, seed quality, soil health, and resource use efficiency in soybean under semi-arid conditions - Chethan Kumar Talavar; Pushpa Krishna; Manjanagouda Siddanagouda Sannagoudar; Krishnamurthy Rangaiah; Hadivappa Marulappa Jayadeva; Vinay Mallikarjuna Gangana Gowdra; Ramya Parakkunnel; Shantharaja Chittanahalli Shivanna; Sripathy Kudekallu Vasudeva; Channappa Gireesh; Anandan Annamalai; Bhojaraja Naik Keshava; et al. (Scientific Reports, 2026)
Abstract Climate change and excessive dependence on the chemical fertilizers have threatened soil fertility, crop productivity and environmental sustainability through soil degradation and desertification. Use of liquid bio-fertilizers are one of the effective ways of improving the soil fertility and nutrient availability. Despite increasing use of liquid fertilizers, comparative information on effective microorganisms and other microbial inoculants with respect to nutrient use efficiency, energy balance and carbon budget in soybean is limited. To enumerate the role of biofertilizer on the soybean yield, seed quality, soil health, energy-carbon dynamics, a two-year field study was conducted during the kharif season of 2024 and 2025 using randomized block design comprising nine seed biopriming treatments with different liquid biofertilizers tested under three replications. The growth, yield and soil biological properties were recorded at different crop growth stages following standard procedures whereas, the carbon and energy inputs and output were calculated by multiplying the inputs and outputs with respective standard coefficients. The result revealed that, seed bio-priming with liquid effective micro-organisms (S 2 ) recorded significantly higher leaf area (2254.58 cm 2 plant −1 ), SPAD values (55.9) and dry matter accumulation (18.49 g plant −1 ) at 60 days after sowing (DAS). Similarly, S 2 recorded significantly higher number of pods plant −1 (28.08%), seed yield (8.3%) and haulm yield (14.6%) over 100% recommended nutrient rate (S 1 ). Seed biopriming with biofertilizers enhanced the soil biological activity with significantly higher microbial population and dehydrogenase activity at S 2 . The comparative climatic advantage of seed biopriming with liquid biofertilizers was observed in all treated plants, among which higher eco efficiency (57.74), carbon efficiency (14.58), net energy (71,213 MJ kg −1 ), energy profitability (0.17) and lower the GHG intensity (0.43) was observed at S 2 . Seed biopriming with liquid biofertilizers sustainably enhanced the soybean productivity with improved soil health while lowering the estimated GHG intensity. The present findings display the potential of liquid biofertilizer based seed priming as a sustainable strategy for enhancing soybean productivity while improving the resource use efficiency and support climate smart practices.